Highly sensitive selectively coated photonic crystal fiber-based plasmonic sensor - Rifat, Ahmmed A.; Haider, Firoz; Ahmed, Rajib Ali; Mahdiraji, Ghafour Amouzad; Adikan, Faisal Rafiq Mahamd; Miroshnichenko, Andrey E. (Optical Society of America, 2018)
Highly sensitive and miniaturized sensors are highly desirable for real-time analyte/sample detection. In this Letter, we propose a highly sensitive plasmonic sensing scheme with the miniaturized photonic crystal fiber (PCF) attributes. A large cavity is introduced in the first ring of the PCFs for the efficient field excitation of the surface plasmon polariton mode and proficient infiltration of the sensing elements. Due to the irregular air-hole diameter in the first ring, the cavity exhibits the birefringence behavior which enhances the sensing performance. The novel plasmonic material gold has been used considering the chemical stability in an aqueous environment. The guiding properties and the effects of the sensing performance with different parameters have been investigated by the finite element method, and the proposed PCFs have been fabricated using the stack-and-draw fiber drawing method. The proposed sensor performance was investigated based on the wavelength and amplitude sensing techniques and shows the maximum sensitivities of 11,000 nm/RIU and 1;420 RIU−1, respectively. It also shows the maximum sensor resolutions of 9.1 × 10−6 and 7 × 10−6 RIU for the wavelength and amplitude sensing schemes, respectively, and the maximum figure of merits of 407. Furthermore, the proposed sensor is able to detect the analyte refractive indices in the range of 1.33–1.42; as a result, it will find the possible applications in the medical diagnostics, biomolecules, organic chemical, and chemical analyte detection.